Efisiensi Keberhasilan Inseminasi Buatan pada Sapi Friesian Holstein di Kota Padang Panjang Tahun 2015 - Ali Akbar, Syahro; Harissatria, Harissatria; Tri Asnita, Mela (Jurnal Peternakan Mahaputra, 2020)
This study aims to determine the efficiency of the success of Artificial Insemination (AI) in Friesian Holsteincattle in Padang Panjang City in 2015. The results of this study can serve as a guideline and reference for breeders andinseminators in implementing AI on Holstein Friesian cattle, so that the value of Conception Rate, Non Efficient ReturnRate and Service Per Conception. The method used is by collecting data on the implementation of AI in HolsteinFriesian cows from the inseminator, the Department of Animal Husbandry and Puskesmas Padang Panjang City. Thedata obtained were analyzed and obtained CR values of 49.62 ± 0.50%, NR values of 75.93 ± 0.43% and S / C values of1.82 ± 0.97. From the research results it can be concluded that the implementation of Artificial Insemination in PadangPanjang is in the efficient category.